2019
DOI: 10.3390/molecules24173068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Olive Extracts on the Expression of Genes Involved in Lipid Metabolism in Medaka Fish

Abstract: Aims. To assess the possible effect of polyphenol-rich olive extracts on lipid metabolism in medaka fish by quantifying the expression of lipogenic and lipolytic genes. Materials and methods. Adult medaka fish were maintained in tanks for five days with five extracts at 0.01% in water, causing obesity through a diet rich in carbohydrates, with a control group maintained in water with a normal diet. The extracts contained polyphenols ranging between 7 and 116 mg/g (oleuropein, hydroxytyrosol) with an antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Cai et al [ 45 ] believed in their study that reducing the level of mRNA and protein in Wnt1 can affect the differentiation of muscle cells, and the expression level of Wnt1 has an important effect on promoting muscle synthesis and reducing fat deposition. The effect of plant extracts on lipid deposition by regulating the expression level of lipid metabolism-related genes has been demonstrated in previous studies [ 46 , 47 ]. At the same time, according to the study of Xu et al [ 48 ], adding different dosages of plant sterols to feed can up-regulate the expression level of Wnt1 mRNA in liver and back muscle of pigs, thereby improving the lean meat rate.…”
Section: Discussionmentioning
confidence: 80%
“…Cai et al [ 45 ] believed in their study that reducing the level of mRNA and protein in Wnt1 can affect the differentiation of muscle cells, and the expression level of Wnt1 has an important effect on promoting muscle synthesis and reducing fat deposition. The effect of plant extracts on lipid deposition by regulating the expression level of lipid metabolism-related genes has been demonstrated in previous studies [ 46 , 47 ]. At the same time, according to the study of Xu et al [ 48 ], adding different dosages of plant sterols to feed can up-regulate the expression level of Wnt1 mRNA in liver and back muscle of pigs, thereby improving the lean meat rate.…”
Section: Discussionmentioning
confidence: 80%
“…Through this, elevated PPARα is known to play a role in fatty acid oxidation, together with CPT1 [40,41]. In addition, ACO1 is known to be an enzyme involved in the initial step of fatty acid oxidation [42]. When these targets promote fatty acid oxidation, oxidized fatty acids appear to work with UCP1 in the mitochondria to enhance thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In teleost fish, palmitoyltransferase has been associated with cold resistance in relation to lipid catabolism and autophagy during fasting, using zebrafish models (Lu et al, 2019), and in fastinginduced fatty acid oxidation in yellow croaker (Wang et al, 2019c). It has furthermore been assessed in lipid metabolism during obesogenic diet using medaka fish (Torró-Montell et al, 2019), while different isoforms have been identified to have roles in grass carp liver during nutritional limitation (Shi et al, 2017). In elasmobranchs, activities of this fatty acid catabolising enzyme was shown to be 5% the rate of what is seen in teleosts, and in hagfish carnitine palmitoyltransferase rate was 10% compared with teleosts (Moyes et al, 1990).…”
Section: Discussionmentioning
confidence: 99%